Pediatric rehabilitation delivery: discussion is an antidote to disconnection and discontent - Maurit Beeri (BMC, 2024)
Abstract Pediatric rehabilitation is fundamentally different from that of adults. Child physiology differs significantly from that of adults, necessitating specialized rehabilitation approaches. Unique injuries and varying metabolic rates underscore the need for tailored care, which changes over the years as the child grows and develops. Waiserberg's paper, "When Everyone is Responsible, No One Takes Responsibility": Exploring Pediatric Physiotherapy Services in Israel," sheds light on a critical issue. While senior practitioners oversee policy implementation and service delivery, practical physiotherapy treatment lacks continuous monitoring. This is a critical issue. Ideally, every child who requires long-term clinical therapeutic interventions to keep up with peers in mobility, communication and cognitive skills should be assessed by specialists several times throughout the school years, and their personalized rehabilitation plan discussed, reviewed, and adjusted according to their progress. The absence of a standardized protocol for overseeing and directing comprehensive rehabilitation plans leaves therapists feeling alone and adrift, whether working in schools or medical settings. Such an assessment would be an opportunity to create a registry, which is currently nonexistent. The collected data would be a priceless resource in policy decision-making and service planning.